Aesthetic Chills: Knowledge-Acquisition, Meaning-Making, and Aesthetic Emotions - Schoeller, Felix; Perlovsky, Leonid (Frontiers in Psychology, 2016)
This article addresses the relation between aesthetic emotions, knowledge-acquisition, and meaning-making. We briefly review theoretical foundations and present experimental data related to aesthetic chills. These results suggest that aesthetic chills are inhibited by exposing the subject to an incoherent prime prior to the chill-eliciting stimulation and that a meaningful prime makes the aesthetic experience more pleasurable than a neutral or an incoherent one. Aesthetic chills induced by narrative structures seem to be related to the pinnacle of the story, to have a significant calming effect and subjects describe a strong empathy for the characters. We discuss the relation between meaning-making and aesthetic emotions at the psychological, physiological, narratological, and mathematical levels and propose a series of hypotheses to be tested in future research.